Etiology, Diagnosis and Treatment of Dentin Hypersensitivity - Sahoo, Subhashree; Govind, Shashirekha (Journal of Biomedical and Pharmaceutical Research, 2024)
The hallmark of dentin hypersensitivity is sudden, intense pain brought on by exposed dentin, frequently resulting from gum recession and enamel loss. The hydrodynamic theory explains the symptoms, which connect fluid movement in dentinal tubules to nerve activity and external stimuli. A survey revealed a prevalence of over 60%, primarily affecting the lower incisors. Dental professionals could be misinformed about it. While management entails a customized strategy that includes professional treatments, self-care products, and oral health guidelines, diagnosis necessitates ruling out alternative reasons. Despite several potential interventions, there is no single or widely acknowledged remedy. Therefore, dentists should continue their education to correctly identify and treat dentin hypersensitivity.KEYWORDS: Dentin hypersensitivity, hydrodynamic theory, exposed tooth, brushing technique, surgical technique